Sistem Informasi Pelaksanaan KKN Berbasis Web di Universitas Negeri Makassar - Muh. Alwi Rizkyansyah Kasim; Muhammad Agung; Jumadi Mabe Parenreng; Mustari S. Lamada; Abdul Wahid (Sakura Publisher, 2024)
The research conducted is Research and Development (R&D). The aim of this study is to determine the results of the development of a web-based Community Service Program Implementation Information System using the prototyping development method. Additionally, the research aims to assess the quality of the developed software using the ISO 25010 standard. The data collection techniques used include questionnaires, interviews, observations, and documentation. This study resulted in a web-based Community Service Program Implementation Information System using the Laravel framework. The testing results indicated good quality, detailed across eight aspects: functional suitability scored 0.956 and 0.978 from the two functionality testers, both of which are categorized as